Public Relations (PR) and Corporate Social Responsibility (CSR) in Malaysia: A critical reflection - Ahmad, Zeti Azreen (2013)
In the 1980s, several key policies were introduced to transform Malaysia from an agricultural based economy to an industrial nation e.g., the ‘Malaysian Incorporated’, ‘Industrialization’ and ‘Privatization’ policies. This study chronicles the early development of public relations (PR) in Malaysia and how government’s key policies have lifted PR to a new height. Drawing from Malaysian experience, it is apparent that PR’s role has gradually changed and expanded to suit a particular context and need, mainly to the advantage of the elites or powerful actors in society. Similarly, the development of corporate social responsibility (CSR) in Malaysia is largely motivated to pursue the interest of the government and business. In this case, PR role in promoting excellent practice in Malaysia and that includes its role in driving CSR would appear problematic. This paper argues that the development of both PR and CSR is determined by the historical, social, economic and political framework of a country. Literatures affirmed that early CSR practice in Malaysia was part of PR activity undertaken by multinational firms to build relationships with the government by supporting various nation building activities (Arun 1993 in Leuven 1996). This study extends the literature by critically examining the actual role of PR in CSR through insights from real PR practitioners in the country. The paper exposes the relationships between corporate social responsibility (CSR) practice and the scope of public relations (PR) in Malaysia. It embraced a critical approach which offers alternate readings of Malaysian PR literature which are dominantly quantitative in nature. The focus is on how historical, socio-political, economic, cultural and organizational contexts shape the practice of CSR and affect the scope and function of PR in pursuing the practice. This study has employed semi-structured interviews among PR and CSR managers working in renowned CSR organizations in the country. In addition, the study analyses executives’ messages in CSR reports and later triangulated with interview findings that helped to achieve a rich description of the topic under study. CSR practice is a recent phenomenon in Malaysia whereby the government has been a major driver in its development. Drawing from history, economic growth is fundamental to ensure a fair distribution of wealth among multi-races in Malaysia that perceived imperative to preserve national unity. In this respect, CSR initiatives have been largely undertaken to achieve the long term survival of businesses that consequently drive the nation’s economy. This has been widely accepted among business firms in Malaysia thus become ideological. At the same time, PR role in promoting the practice of CSR was found central. More often than not, such role appears to be working to the advantage of the dominant groups i.e., business and government. Nevertheless, how PR promotes mutual interests of business and society through CSR remain obscure. Among others, CSR initiative in Malaysia could be seen as a state project that promotes government’s aspiration to develop the nation. The finding of this study was a clear example that CSR development is parallel to the history, socio-cultural and values hold by a specific nation thus the practice remains distinctive in its own way.